2010
DOI: 10.1177/000313481007600704
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Mucormycosis as a Cause of Life-Threatening Upper Gastrointestinal Bleeding in a Trauma Patient

Abstract: Letters to the Editor should be submitted online to www.editorialmanager.com/ amsurg. (See details online under ''Instructions for Authors''.) They should be no more than 3 double-spaced pages excluding an Abstract and sub-headings with a maximum of four (4) references. If figures are included, they should be limited to two (2). The cost of printing color figures is the responsibility of the author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Surgical intervention for disseminated infections is a grade CIII recommendation. 20 These recommendations do not specifically address GI infections or invasive infections, as in our case.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Surgical intervention for disseminated infections is a grade CIII recommendation. 20 These recommendations do not specifically address GI infections or invasive infections, as in our case.…”
Section: Discussionmentioning
confidence: 92%
“…Other antifungals, such as fluconazole, voriconazole, itraconazole, echinocandins, flucytosine, terbinafine are not currently supported for use in the treatment of mucormycosis. 20 Cresemba (isavuconazonium sulfate), ergosterol inhibitor, was recently approved for the treatment of invasive mucormycosis and aspergillosis that offers an extended spectrum antifungal activity with promising early study results. 22.23 These findings provide an avenue for more research into GI mucormycosis in immunocompetent adults in the future, as well as for guidelines for adequate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the tissue diagnosis was not obtained until after the patient’s condition had deteriorated. To date, there have only been four case reports of invasive Mucormycosis involving trauma patients that presented either as a cutaneous lesion or as a GI bleed [14] , [15] , [16] , [17] . We emphasize the importance of having a high clinical suspicion to obtain early histopathologic diagnosis of this rare disease to initiate the proper treatment of surgical debridement, intravenous antifungals, and improve outcomes from this deadly infection.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the cases of gastrointestinal mucormycosis were reported from the tropics; however, the disease is increas­ingly becoming an iatrogenic and/or nosocomial problem in industrialized nations [ 7 ] and recent studies have reported dramatic increase in the incidence of mucormycosis [ 22 - 24 ]. Very few cases of gastrointestinal mucormycosis affecting adults have been reported in the United States [ 6 , 7 , 25 ].…”
Section: Discussionmentioning
confidence: 99%